PELAKSANAAN FUNGSI OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU - Anggraini, Tutut Mauludtias; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Ombudsman of the Republic of Indonesia functions to oversee the administration of public services organized by public service providers organized by state and government officials both at the central and regional levels, including those held by State-Owned Enterprises, Regional-Owned Enterprises, and State-Owned Legal Entities and private or individuals who are given the task of carrying out certain public services. To expedite its duties and functions as a supervisory institution for the implementation of public services, the Ombudsman formed a representative in Riau Province. The purpose of this study is to find out how the implementation of the Ombudsman function of the Republic of Indonesia Representative Province of Riau, especially in the field of land and the factors that hinder it. The theory used is the theory of Sule and Saefullah namely there are four indicators of the steps of the supervision process. The results of this study indicate that: first, the implementation of the Ombudsman RI Republic of Riau's Representative Function is not optimal due to obstacles such as the complexity of community report settlement in the field of land involving many parties and a long process of settlement, so there are still reports that the Ombudsman has not yet completed and are a burden The Ombudsman for the following year, and in its oversight function is not optimal because in the prevention of maladministration activities, the Ombudsman has not been able to suppress the number of maladministration that occurs in Riau Province. Second, the factors that hinder the implementation of the Indonesian Ombudsman Representative Function in Riau Province namely: lack of human resources and limited budget.                                                                                                                         Keywords: Implementation, Function, Ombudsman.